2017
DOI: 10.18632/oncotarget.15186
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic interrogation as a tool to optimize chemotherapeutic regimens

Abstract: Platinum-based (Pt) chemotherapy is broadly utilized in the treatment of cancer. Development of more effective, personalized treatment strategies require identification of novel biomarkers of treatment response. Since Pt compounds are inactivated through cellular metabolic activity, we hypothesized that metabolic interrogation can predict the effectiveness of Pt chemotherapy in a pre-clinical model of head and neck squamous cell carcinoma (HNSCC).We tested the effects of cisplatin (CDDP) and carboplatin (CBP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…13 C flux experiments demonstrated higher glucose uptake and flux into 3-carbon intermediates and TCA cycle intermediates, with decreased incorporation into pentose phosphate pathway (PPP) intermediates in the cisplatin-resistant cells consistent with increased overall catabolic activity ( Figure 5 ). The Warburg effect (conversion of glucose into lactate) was similar between parental and cisplatin resistant cells, consistent with our previous work [ 8 , 9 , 10 , 11 ]. However, cisplatin resistant cells demonstrated drastically different rates of serine and aspartate catabolism and synthesis ( Figure 5 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…13 C flux experiments demonstrated higher glucose uptake and flux into 3-carbon intermediates and TCA cycle intermediates, with decreased incorporation into pentose phosphate pathway (PPP) intermediates in the cisplatin-resistant cells consistent with increased overall catabolic activity ( Figure 5 ). The Warburg effect (conversion of glucose into lactate) was similar between parental and cisplatin resistant cells, consistent with our previous work [ 8 , 9 , 10 , 11 ]. However, cisplatin resistant cells demonstrated drastically different rates of serine and aspartate catabolism and synthesis ( Figure 5 ).…”
Section: Resultssupporting
confidence: 92%
“…Over the last decade, we have shown that generation of oxidative stress either through application of ionizing radiation (IR) or platinum derivatives triggers acute, reversible metabolic changes in a variety of tumor models including HNSCC [7][8][9][10]. This has allowed us to develop a relatively quantitative, albeit indirect relationship between metabolic perturbations linked to carbon flux and generation of intra-cellular oxidative stress and DNA damage [7][8][9][10]. Initially, this relationship was limited to the most common metabolic reaction common to solid tumors, namely the conversion of pyruvate into lactate, the lynchpin of the Warburg effect [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, cisplatin adds a benefit to radiotherapy, with significant improvement of overall survival at five years in head and neck SCC patients 35,36 . It is known that cisplatin treatment increases the duration of S phase and arrests cells in the G 2 /M phase 8,34,[37][38][39] , which could contribute to radiosensitization. In the present study we share similar observations.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of TP53 mutation on HNSCC biology and response to treatment has been thoroughly documented by our group and others using both pre-clinical disease models and retrospective patient cohorts. (8,9,11,13,15,2426) TP53 mutations can behave in a heterogeneous manner with response to both tumorigenesis and treatment response. (8,9,14) Most recently, we developed an evolutionarily-based scoring system to classify TP53 mutations as: 1) “low-risk” missense mutations, 2) “high-risk” missense mutations, and 3) “other” TP53 mutations (e.g.…”
Section: Discussionmentioning
confidence: 99%